Prevention of central venous line-related thrombosis by continuous infusion of low-dose unfractionated heparin, in patients with haemato-oncological disease - Abdelkefi, Abderrahman; Ben Othman, Tarek; Kammoun, Leïla; Chelli, Mouna; Ben Romdhane, Neïla; Kriaa, Azza; Ladeb, Saloua; Torjman, Lamia; Lakhal, Amel; Achour, Wafa; Ben Hassen, Assia; Hsaïri, Mohamed; Ladeb, Fethi; Ben Abdeladhim, Abdeladhim (Thrombosis and Haemostasis, 2004)
We have conducted a prospective randomized controlled trial to evaluate the role of low-dose unfractionated heparin prophylaxis in preventing central venous line-related thrombosis in patients with haemato-oncological disease. Patients were randomly assigned to receive either prophylactic intravenous unfractionated heparin (continuous infusion of 100 IU/kg/daily) or 50 ml/daily of normal saline solution as a continuous infusion. CVLs were externalized, non tunneled, double lumen catheters. All CVLs were placed percutaneously by the same physician in the subclavian vein. Upper limb veins were systematically examined by ultrasonography just before, or < 24 hours after, catheter removal, and in case of clinical signs of thrombosis. One hundred and twenty-eight CVLs were inserted. Catheterrelated thrombosis occurred in 1.5% of the catheters inserted in patients of the heparin group, and in 12.6% in the control group (p = 0.03). No other risk factors were found for the development of catheter-related thrombosis. Two and three patients experienced severe bleeding in the heparin group, and in the control group, respectively (p = 0.18). There were no other side-effects clearly ascribable to the use of unfractionated heparin. This is the first prospective, randomized study, which shows that low-dose of unfractionated heparin is safe and effective to prevent catheter-related thrombosis in patients with haemato-oncological disease.
Keywords: Central venous catheter; thrombosis; heparin